Obesity and youth diabetes: distinguishing characteristics between islet cell antibody positive vs. negative patients over time. Issue 5 (5th December 2014) - Rivera‐Vega, Michelle Y; Flint, Amanda; Winger, Daniel G; Libman, Ingrid; Arslanian, Silva
<x xml:space="preserve">Abstract</x> Objective Obese youth clinically diagnosed with type 2 diabetes mellitus (T2DM) frequently have evidence of islet cell autoimmunity. We investigated the clinical and biochemical differences, and therapeutic modalities among autoantibody positive (Ab+) vs. autoantibody negative (Ab−) youth at the time of diagnosis and over time in a multi‐provider clinical setting. Study design Chart review of 145 obese youth diagnosed with T2DM from January 2003 to July 2012. Of these, 70 patients were Ab+ and 75 Ab−. The two groups were compared with respect to clinical presentation, physical characteristics, laboratory data, and therapeutic modalities at diagnosis and during follow up to assess the changes in these parameters associated with disease progression. Results At presentation, Ab+ youth with a clinical diagnosis of T2DM were younger, had higher rates of ketosis, higher hemoglobin A1c (HbA1c) and glucose levels, and lower insulin and c‐peptide concentrations compared with the Ab− group. The Ab− group had a higher body mass index (BMI) z‐score and cardiometabolic risk factors at diagnosis and such difference remained over time. Univariate analysis revealed that treatment modality had no effect on BMI in either group. Generalized estimating equations for longitudinal data analysis revealed that (i) BMI z‐score and diastolic blood pressure (DBP) were significantly affected by duration of diabetes; (ii) systolic blood pressure (SBP) and ALT were affected by changes in BMI z‐score; and (iii) changes in HbA1c had an effect on lipid profile and cardiometabolic risk factors regardless of antibody status. Conclusions Irrespective of antibody status and treatment modality, youth who present with obesity and diabetes, show no improvement in obesity status over time, with the deterioration in BMI z‐score affecting blood pressure (BP) and ALT, but the lipid profile being mostly impacted by HbA1c and glycemic control. Effective control of BMI and glycemia are needed to lessen the future macrovascular complications irrespective of antibody status.